2017
DOI: 10.3390/children4070054
|View full text |Cite
|
Sign up to set email alerts
|

Sino-Nasal 5 Questionnaire is Associated with Poor Asthma Control in Children with Asthma

Abstract: Up to 80% of asthmatic children may experience upper airway symptoms which are often perceived as coming from the lower airways. Currently, there are no validated questionnaires to assess upper airway contribution to pediatric asthma symptoms. The Sino-Nasal 5 (SN-5) questionnaire was previously validated for identifying radiographic confirmed sinus disease in children. In this study, we hypothesize that significant SN-5 scores (≥3.5) are associated with abnormal National Asthma Education and Prevention Progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…These results are consistent with the concept of “One airway, one disease” and testify to a potential commonality of involvement in the pathological process in the BA of the upper and lower respiratory tract [ 17 ]. The new data obtained are in good agreement with the studies of Huang et al [ 24 ], Thorstensen et al [ 31 ], and Kilaikode et al [ 32 ], which stress the importance of upper respiratory pathology in the management of patients with asthma. Thus, our study is a confirmation of the concept of “United Airways,” which indicates that for patients with inflammation of the lower respiratory tract, parallel inflammation in the upper respiratory tract is characteristic.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with the concept of “One airway, one disease” and testify to a potential commonality of involvement in the pathological process in the BA of the upper and lower respiratory tract [ 17 ]. The new data obtained are in good agreement with the studies of Huang et al [ 24 ], Thorstensen et al [ 31 ], and Kilaikode et al [ 32 ], which stress the importance of upper respiratory pathology in the management of patients with asthma. Thus, our study is a confirmation of the concept of “United Airways,” which indicates that for patients with inflammation of the lower respiratory tract, parallel inflammation in the upper respiratory tract is characteristic.…”
Section: Discussionsupporting
confidence: 91%
“…In the study of Huang et al [ 24 ] and Thorstensen et al [ 31 ], a statistically significant relationship was established between the level of control of asthma and the expression of synonasal symptoms in adult patients with asthma [ 24 , 31 ]. A study by Kilaikode et al demonstrated a link between synonasal symptoms and the level of asthma control in children, but this study did not provide a description of the pathology of the upper respiratory tract, taking into account its multimorbidity [ 32 ]. In the work of Chen et al [ 33 ], patients with anatomical deformities affecting the patency of the upper respiratory tract were excluded from the cohort for the study of nasal symptoms, rhinomanometric indices, and markers of inflammation in asthmatic children.…”
Section: Introductionmentioning
confidence: 99%
“…As previously described ( 15 , 16 ), asthma was defined using National Asthma Education and Prevention Program (NAEPP) guidelines for the diagnosis, classification, and management of asthma in children, which stratify asthma severity based on clinical impairment (daytime and nighttime symptoms, activity limitation, and lung function testing) ( 17 ). Clinical classification of asthma severity was conducted independently and blinded to cytokine data analyses.…”
Section: Methodsmentioning
confidence: 99%